The Effect of Related Party Transactions, Tax Planning, And Leverage Moderated By Independent Commissioners On Earnings Management - Reza Ramadhan; Agus Bandiyono (Green Publisher Indonesia, 2024)
Managers carry out earnings management with various motives to get the desired profit level so that the company's financial statements do not reflect the actual situation. The purpose of this study is to determine the effect of related party transactions, tax planning, and leverage on earnings management, as well as the role of independent commissioners in moderating this effect. This study tested manufacturing sector companies listed on the Indonesia Stock Exchange during 2016-2019 with a total sample of 220 samples using a purposive sampling method. The type of data used is secondary data obtained from www.idx.co.id. This study uses two panel data regression models, namely models with and without moderation. The results of this study indicate that related party transactions have a negative effect on earnings management, while tax planning and leverage have no effect on earnings management. Furthermore, independent commissioners can moderate the effect of related party transactions, tax planning, and leverage on earnings management.